Music Therapy for Children with Oncology & Hematological Conditions and Their Families: Advancing the Standards of Psychosocial Care. (January 2022) - Knott, David; Krater, Caitlin; MacLean, Jessica; Robertson, Kim; Stegenga, Kristin; Robb, Sheri L.
Background: Diagnosis and treatment of cancer and blood disorders in childhood, adolescence and young adulthood has a significant impact on patients and families. The Psychosocial Standards of Care project, initiated in 2012, resulted in 15 Psychosocial Standards (PSS) that guide the care patients and families receive throughout treatment. As members of the multidisciplinary psychosocial care team, music therapists play an important role in the advancing the PSS. Most surveys have focused on other commonly provided services (e.g., social work, child life), leaving gaps in our understanding about the availability and use of music therapy services to advance PSS. This paper offers an initial description of how music therapy services contribute to the provision of care under these Standards.Methods: We analyze how music therapy services promote PSS through synthesis of a music therapy clinical practice survey, published literature, and scope of practice documents. A brief overview of music therapy services structure, PSS that music therapy services currently address, and two clinical program descriptions are included.Results: Music therapy services address 9 of the 15 PSS and are well integrated within the larger program of psychosocial care. Findings suggest integration of music therapy services can help ensure personalized, comprehensive care and efficient use of often-limited psychosocial care resources.Discussion: Nurses, as members of the psychosocial and medical teams are uniquely positioned to identify patient and family care needs and refer patients for services. Understanding how music therapy services address PSS and most importantly, the needs of patients and families, will optimize their care.